Factors influencing learner autonomy and autonomy support in a faculty of education - Basri, Fatma (Routledge Journals, Taylor & Francis Ltd, 2023)
Most studies on learner autonomy are in language learning while those on autonomy support are in secondary schools, and are mainly of quantitative nature conducted with either teachers or learners. However, in-depth qualitative studies focusing on the factors influencing learner autonomy in higher education and autonomy support provided for student teachers by teacher educators are scarce. Drawing on data from a qualitative study carried out in an education faculty, this article focuses on both teacher educators' and student teachers' perceptions of the factors that limit learner autonomy practice and support. The findings suggest teacher/learner backgrounds, mismatch between teacher and learner expectations, spoon-feeding tendencies of teachers, limited teacher autonomy and large classes are the main factors. The findings also suggest that there exists a dynamic interaction between the constructs of learner autonomy, teacher support and teacher autonomy indicating these need to be treated together rather than in isolation.
Keywords: Learner autonomy; teacher support; factors; teacher autonomy; perspectives; higher education